Cubanness, Exile and Artist in Héctor Santiago’s La memoria del agua (2023)
The article investigates the Cubanness linked to the figure of the exiled and the artist as a condition of life that establishes geographical and border consciousness. We interpret La memoria del agua by Héctor Santiago based on the crosscultural modality of Ortiz (Contrapunteo) the epistemological location of Mignolo (La idea) and the border consciousness of Anzaldúa to demonstrate how the Cubanness of the exiled endeavors to configure the geographical consciousness and logic of the border. The character from Santiago, therefore, exists both as an exiled and an artist since he lives the triple existential condition of the cage, flight and return. This represents in La memoria del agua the place and moment of Cubanness. We discover that Cubanness is based on the conscious attitude of the exiled, whose purpose is to establish the existence of a geographical consciousness that includes also the consciousness of the border.